Mantra for Real success in life - Malik, Shiv; Aneet (Gyan Management Journal, 2015)
What are the qualities, habits and attitudes lead to sustained success and not merely an ephemeral one? How can we get these traits? Mere brilliance and hard work does not guarantee outstanding success. How then does one reach the top? There is life beyond success. How does one achieve the inscrutable balance? What makes us a complete woman/ man? This book answers these questions. It is not possible for us to live a perfect life, but one can always learn to lead a reasonably successful life following certain principles based on good values. People approach the subject of personal development differently, while aspiring to live a quality life. This book is a refreshing departure from the run-of-the-mill books in more than one way. The author of the book has practiced in his life what he wants his readers to follow. His approach is anecdotal with emphasis on drawing right lessons. Also the author’s claim that his inspiration to write the book was to share his work-life experiences with his 17 year-old-grandson lends credibility and authenticity to what he says.